2007
DOI: 10.1057/palgrave.crr.1550050
|View full text |Cite
|
Sign up to set email alerts
|

The Role Concept in Corporate Branding and Stakeholder Management Reconsidered: Are Stakeholder Groups Really Different?

Abstract: In many cases, research in corporate branding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Although they acknowledge that a relationship between CSR and shareholder evaluations may represent a judgment that managers are dealing effectively with stakeholders, ' such an overall relationship cannot be asserted until the strands that make it up -the links among stakeholder expectations, effects, evaluations, and behaviors with respect to a fi rm -have been delineated ' ( Wood and Jones, 1995: 242 ). Different stakeholder groups will view the fi rm and its activities from different perspectives based on their own interests and expectations ( Fiedler and Kirchgeorg, 2007 ;Hillenbrand and Money, 2007 ). This potential for confl icting expectations, effects, evaluations and behaviors has led researchers to call for a contingent approach to the study of CSR (eg, Rowley and Berman, 2000 ); to ' recast the question to investigate the con ditions under which stakeholders will take action to infl uence the focal organization and when those actions will infl uence the CSP-[C]FP link ' ( Rowley and Berman, 2000: 397 ).…”
Section: Stakeholder Evaluations Of Csrmentioning
confidence: 99%
“…Although they acknowledge that a relationship between CSR and shareholder evaluations may represent a judgment that managers are dealing effectively with stakeholders, ' such an overall relationship cannot be asserted until the strands that make it up -the links among stakeholder expectations, effects, evaluations, and behaviors with respect to a fi rm -have been delineated ' ( Wood and Jones, 1995: 242 ). Different stakeholder groups will view the fi rm and its activities from different perspectives based on their own interests and expectations ( Fiedler and Kirchgeorg, 2007 ;Hillenbrand and Money, 2007 ). This potential for confl icting expectations, effects, evaluations and behaviors has led researchers to call for a contingent approach to the study of CSR (eg, Rowley and Berman, 2000 ); to ' recast the question to investigate the con ditions under which stakeholders will take action to infl uence the focal organization and when those actions will infl uence the CSP-[C]FP link ' ( Rowley and Berman, 2000: 397 ).…”
Section: Stakeholder Evaluations Of Csrmentioning
confidence: 99%
“…In addition, the contribution addresses two further concerns with regard to existing measurement tools articulated by Bromley (2002): The first is Bromley's skepticism of overall scores of reputation, such as the RQ and the Fortune measures, which are derived from applying exactly the same model of reputation across different stakeholder groups. Research has shown that stakeholder groups are likely to differ in their values and beliefs and are therefore likely to judge a company's reputation in terms of different issues that are important to them (Fiedler and Kirchgeorg 2007). Bromley's other criticism is of reputation scores or rankings that are derived from the sum or average of scores on a number of sub-scales.…”
Section: Introductionmentioning
confidence: 98%
“…First, an amalgamation approach ignores the fact that different stakeholders are likely to use differing—often self‐serving—criteria in their reputation evaluations (Rindova et al ; Sjovall and Talk ). Indeed, research has demonstrated that marketers are best advised to cater to the different attributes among stakeholder groups (Fiedler and Kirchgeorg ). This implies that stakeholders differ in what they value within organizations (Hillenbrand et al ).…”
Section: Introductionmentioning
confidence: 99%